CDKN1C‐mediated growth inhibition by an EZH1/2 dual inhibitor overcomes resistance of mantle cell lymphoma to ibrutinib. Issue 6 (1st May 2021) - Kagiyama, Yuki; Fujita, Shuhei; Shima, Yutaka; Yamagata, Kazutsune; Katsumoto, Takuo; Nakagawa, Makoto; Honma, Daisuke; Adachi, Nobuaki; Araki, Kazushi; Kato, Ayako; Inaki, Koichiro; Ono, Yoshimasa; et al.
Abstract: Mantle cell lymphoma (MCL) is a rare subtype of non‐Hodgkin's lymphoma, which is characterized by overexpression of cyclin D1. Although novel drugs, such as ibrutinib, show promising clinical outcomes, relapsed MCL often acquires drug resistance. Therefore, alternative approaches for refractory and relapsed MCL are needed. Here, we examined whether a novel inhibitor of enhancer of zeste homologs 1 and 2 (EZH1/2), OR‐S1 (a close analog of the clinical‐stage compound valemetostat), had an antitumor effect on MCL cells. In an ibrutinib‐resistant MCL patient–derived xenograft (PDX) mouse model, OR‐S1 treatment by oral administration significantly inhibited MCL tumor growth, whereas ibrutinib did not. In vitro growth assays showed that compared with an established EZH2‐specific inhibitor GSK126, OR‐S1 had a marked antitumor effect on MCL cell lines. Furthermore, comprehensive gene expression analysis was performed using OR‐S1–sensitive or insensitive MCL cell lines and showed that OR‐S1 treatment modulated B‐cell activation, differentiation, and cell cycle. In addition, we identified Cyclin Dependent Kinase Inhibitor 1C (CDKN1C, also known as p57, KIP2), which contributes to cell cycle arrest, as a direct target of EZH1/2 and showed that its expression influenced MCL cell proliferation. These results suggest that EZH1/2 may be a potential novel target for the treatment of aggressive ibrutinib‐resistant MCL via CDKN1C‐mediated cell cycle arrest. Abstract : This study reveals that oral administration of OR‐S1 significantly suppressed tumor growth in an ibrutinib‐resistant mantle cell lymphoma (MCL) patient–derived xenograft mouse model. OR‐S1 induces cell cycle arrest via the upregulation of CDKN1C. CDKN1C expression was directly regulated by enhancer of zeste homologs 1 and 2 (EZH1/2).